Yttria and Ceria Doped Zirconia Thin Films Grown by Pulsed Laser Deposition - Saporiti, F. (2013)
The Yttria stabilized Zirconia (YSZ) is a standard electrolyte for solid oxide fuel cells (SOFCs), which are potential candidates for next generation portable and mobile power sources. YSZ electrolyte thin films having a cubic single phase allow reducing the SOFC operating temperature without diminishing the electrochemical power density. Films of 8 mol % Yttria stabilized Zirconia (8YSZ) and films with addition of 4 weight % Ceria (8YSZ + 4CeO2) were grown by pulsed laser deposition (PLD) technique using 8YSZ and 8YSZ + 4CeO2 targets and a Nd-YAG laser (355 nm). Films have been deposited on Soda-Calcia-Silica glass and Si(100) substrates at room temperature. The morphology and structural characteristics of the samples have been studied by means of X-ray diffraction and scanning electron microscopy. Films of a cubic-YSZ single phase with thickness in the range of 1-3 µm were grown on different substrates.